Economic impact of ovine footrot and serological diversity and virulence of Dichelobacter nodosus in north Kashmir, India - KABLI, Z A; WANI, S A; HUSSAIN, I; BHAT, M A; RATHER, M A; MAGRAY, S N (The Indian Journal of Animal Sciences, 2014)
The present study was aimed to determine the prevalence and economic impact of footrot as well as to determine the serological diversity and strain differentiation of Dichelobacter nodosus in north Kashmir, India, comprising district Baramulla, Bandipora and Kupwara. The overall prevalence was 14.77% with the estimated economic impact to the tune of Rs 41 million annually to the sheep production in north Kashmir. The prevalence was highest (17.41%) in district Kupwara and lowest (12.71%) in district Bandipora while district Baramulla recorded a prevalence rate of 14.44%. Out of 300 samples collected from footrot lesions of naturally infected sheep, 150 detected positive for D. nodosus by PCR. Over all prevalence of serogroups B, E and I of D. nodosus was 92.7, 32 and 26%, respectively. Infection due to single serogroup was found in 87 samples while, 63 samples revealed mixed infection of 2 or 3 serogroups. Out of 226 isolates of D. nodosus from positive samples, 139 (61.50%) belonged to serogroup B, 48 (21.23%) to E and 39 (17.25%) to I. Virulence characterization revealed that 66.80% showed the presence of integrase (intA) gene, thus were considered as virulent strains. Serogroup wise intA gene was found in 91 (65.46%) isolates of serogroup B, 33 (68.75%) of E and 27 (69.23%) of I. These findings suggested the need for incorporation of serogroups B and E in the formulation of a vaccine to effectively combat footrot in north Kashmir.